2020
DOI: 10.1038/s41598-020-74027-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sulfur components enhancing the anti-Candida effect of Lactobacillus rhamnosus Lcr35

Abstract: GYNOPHILUS (Lcr REGENERANS) is a live biotherapeutic product (LBP) aimed at restoring the vaginal microbiome and contains the live biotherapeutic microorganism Lactobacillus rhamnosus Lcr35. In this study, the LBP formulation and manufacturing process significantly enhanced the anti-Candida activity of L. rhamnosus Lcr35, with a complete loss of viability of the yeast after 48 h of coincubation. Sodium thiosulfate (STS), one excipient of the product, was used as a potentiator of the anti-Candida spp. activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Similarly, Dausset et al, 2020 [ 27 ] demonstrated that the supernatant of Lacticaseibacillus rhamnosus Lcr35 inhibited the growth of Candida albicans ATCC 10231, thus reducing the viability by 3 log10 (CFU/mL). This suggests that the presence of metabolites produced by this probiotic exerts an antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Dausset et al, 2020 [ 27 ] demonstrated that the supernatant of Lacticaseibacillus rhamnosus Lcr35 inhibited the growth of Candida albicans ATCC 10231, thus reducing the viability by 3 log10 (CFU/mL). This suggests that the presence of metabolites produced by this probiotic exerts an antimicrobial effect.…”
Section: Discussionmentioning
confidence: 99%
“…With this decision made, the next step is to choose a formulation, presumably a cream/ointment for local application or a capsule/tablet for vaginal insertion. These present their own challenges, but there have been studies on lactobacilli in creams [35,36] and two products have been approved for intravaginal instillation in Canada [37][38][39] . One of the strains, Lacticaseibacillus rhamnosus Lcr35, was chosen because of properties believed to be suitable for vaginal application, namely anti-Candida activity described in a series of experimental studies [40] .…”
Section: How To Deliver the Strain(s)?mentioning
confidence: 99%
“…Until now, the molecular mechanisms responsible for the anti-pathogenic activity of L. rhamnosus Lcr35 ® have been little described in the literature. The work of Dausset et al (2020) was interested in the mechanisms of action of Gynophilus, a Live Biotherapetic Product (LBP) containing L. rhamnosus Lcr35 ® and sodium thiosulfate, an excipient of the product which potentiate the anti-Candida activity. Thanks to a volatolomic analysis, the authors thus managed to demonstrate the production of a sulfur metabolite, S-methylthioacetate, with fungicidal activity and whose synthesis by L. rhamnosus Lcr35 ® is strongly induced by sodium thiosulfate (Dausset et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The work of Dausset et al (2020) was interested in the mechanisms of action of Gynophilus, a Live Biotherapetic Product (LBP) containing L. rhamnosus Lcr35 ® and sodium thiosulfate, an excipient of the product which potentiate the anti-Candida activity. Thanks to a volatolomic analysis, the authors thus managed to demonstrate the production of a sulfur metabolite, S-methylthioacetate, with fungicidal activity and whose synthesis by L. rhamnosus Lcr35 ® is strongly induced by sodium thiosulfate (Dausset et al, 2020). Although reaching a milestone in the understanding of the mechanism of action, these results did not allow for the moment to describe the molecular anti Candida albicans mechanisms set up by the native strain of L. rhamnosus Lcr35 ® .…”
Section: Introductionmentioning
confidence: 99%